Estimating the age of the adult stages of the blow flies Lucilia sericata and Calliphora vicina (Diptera: Calliphoridae) by means of the cuticular hydrocarbon n-pentacosane. Issue 5 (September 2017) - Bernhardt, Victoria; Pogoda, Werner; Verhoff, Marcel A.; Toennes, Stefan W.; Amendt, Jens
Abstract: Age estimation of insects like blow flies plays an important role in forensic entomology and can answer questions in regard to time of death. So far the focus is on the immature stages of these insects, but recently the adult fly became a target of interest. It has been established that the profile of specific cuticular hydrocarbons (CHCs) changes in a consistent pattern as adult insects age; thus, their analysis could be a promising tool for the age estimation of adult insects. We investigated the CHC n -pentacosane (nC25) on the legs of the adult blow flies Lucilia sericata and Calliphora vicina with gas chromatography–mass spectrometry. The flies were kept at room temperature (17 °C ± 2 °C) and 12:12 L:D from Day 1 to Day 20 post-emergence. For each of five flies per species, the amount of nC25 on all legs was determined daily. The amounts of nC25 on C. vicina increased linearly (R 2  = 0.949). No significant difference between sexes could be detected. While L. sericata showed the same linear increase in general, we found significant (p < 0.001) differences in the amount of nC25 between males and females. Although the amounts of nC25 increased linearly for both sexes (males: R 2  = 0.948; females: R 2  = 0.920), female L. sericata produced more nC25 than males. An equation for the prediction of fly age is constructed from these data. Although the influence of various environmental factors, e.g., fluctuating temperatures, still needs to be tested, nC25 seems to be a promising tool for the age estimation of adult flies. Highlights: Identification of n -pentacosane on legs of two forensically important blow flies Absolute abundance increased during aging in adult flies. New tool for expanding the minimum post-mortem interval in indoor scenes